An interactive, multimedia, web-based program to develop proficiency in specific reading skills for English first-year university students : an empirical study - Buys, Nelia (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Modern Foreign Languages))--University of Stellenbosch, 2004.